Thermodynamics of irreversible processes - Kuiken, G. D. C.
Thermodynamics of irreversible Processes provides a thorough treatment of the basic axioms of irreversible systems and deals with specific applications to diffusion of liquids and matter in flow. This volume will prove to be invaluable reading for anyone working in the field of irreversible phenomena